Synchronous detection of heavy metal ions in aqueous solution by gold nanoparticle surface-enhanced laser-induced breakdown spectroscopy. Issue 12 (21st October 2021) - Yao, Yaqian; He, Fan; Lin, Qingyu; Tian, Yonghui; Zhang, Tianlong; Xu, Boping; Qi, Xinyuan; Duan, Yixiang
Abstract : Heavy metal ion-induced water pollution has become a severe environmental problem in the world. Abstract : Heavy metal ion-induced water pollution has become a severe environmental problem in the world. Although providing a powerful technique for multi-element detection, laser-induced breakdown spectroscopy (LIBS) suffers from insufficient sensitivity for detecting heavy metal ions in aqueous solution due to water splashing and surface ripples. In this work, a simple and sensitive method called gold nanoparticle (AuNP) surface-enhanced laser-induced breakdown spectroscopy (SELIBS) was proposed to detect trace or ultra-trace heavy metal ions in aqueous solutions using a portable instrument. Firstly, the coulombic force allows the adhesion of negatively charged AuNPs and cationic amphiphilic solutions to capture heavy ions, thereby directly improving signal intensity. Interestingly, AuNP size-dependent signal enhancement was found in heavy metal ions through LIBS. To be specific, the signal intensity of Cu, Pb, and Cr increased by 9, 23, and 26 times, respectively, under the optimal AuNP size with a diameter of 13 nm compared to that of the pure target solution. Although the sizes of AuNPs did not affect the plasma temperature and electron density, the local electric field and coulombic force effectively enhanced the LIBS signal. Under optimized experimental conditions, the proposed method achieves sensitive detection of heavy metal ions of Cu, Pb, and Cr with low detection limits (LODs) of 5 ng mL −1, 22 ng mL −1, and 9 ng mL −1, respectively. Moreover, the recoveries of all analytical elements in environmental water samples were analyzed by the standard addition method. The recoveries were in the range of 92.70–100.19%, which further proves the feasibility and potential of surface-enhanced laser-induced breakdown spectroscopy of AuNPs in analyzing actual liquid samples.